DIGITAL STORY TELLING: STUDENTS’ PERCEPTION IN DEVELOPING DESCRIPTIVE WRITING ABILITY - Rizki Nurfida Pambayun; Saiful Anwar (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study is exploring the students’ perception in developing descriptive writing ability trough digital story telling in university students. This study is exploring university students’ perception when they developing their writing especially descriptive text using digital story telling media. The students’ perception is affected how their attitude during activity when they develop their writing ability towards digital story telling media. This study involves 23 participants taken from some classes in English education students which they already practice their descriptive writing using digital story media. This study utilizes a survey using adapted questionnaire and interviews to gather information about the students’ perception regarding their attitude while develop their descriptive writing using digital story telling media. then analysed using likers scale for questionnaire using the formula P = F/N × 100%, and data analysis of interview will be used systematically coded, in which specific statements are analysed and categorized into themes that reflect the phenomenon under investigation. The result of questionnaire shows that almost 80% students give positive perception in digital story telling as media in develop descriptive writing and the result of interview shows that the average students response stated that 75% of students has good perception about digital story telling used in descriptive writing then 25% is neutral. Based on both questionnaire and interview result we can concluded that digital storytelling gives positive perception in developing descriptive writing ability.